2005
DOI: 10.1095/biolreprod.105.043893
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Intrauterine Growth Restriction by Reducing Placental Vascular Growth with the Angioinhibin TNP-470

Abstract: The placenta is a specialized vascular interface between the maternal and fetal circulations that increases in size to accommodate the nutritional and metabolic demands of the growing fetus. Vascular proliferation and expansion are critical components of placental development and, consequently, interference with vascular growth has the potential to severely restrict concurrent development of both the placenta and fetus. In this study, we describe the effects of an antiangiogenic agent, TNP-470, on placental va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 63 publications
4
23
0
2
Order By: Relevance
“…A previous study has shown that administration of the angiogenesis inhibitor TNP-470 to pregnant mice from day 10.5 to 18.5 results in diminished placental and fetal growth (21). The morphological analysis performed by the authors revealed that TNP-470 disturbed labyrinthine blood vessel growth in the placenta.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…A previous study has shown that administration of the angiogenesis inhibitor TNP-470 to pregnant mice from day 10.5 to 18.5 results in diminished placental and fetal growth (21). The morphological analysis performed by the authors revealed that TNP-470 disturbed labyrinthine blood vessel growth in the placenta.…”
Section: Discussionmentioning
confidence: 89%
“…Indeed, overexpression of sFlt-1 and administration of TNP-470, an angiogenesis inhibitor, in pregnant animals impaired the placental vascular development and caused IUGR (18,21). Both decreased placental blood flow and the inhibitor delivered to the fetus may influence the fetal vascular development and result in changes to the architecture of the vascular network.…”
Section: Introductionmentioning
confidence: 99%
“…Noha az érképződési zavar teljes mechanizmusának biológiai háttere egyelőre felderítetlen, az angiogeneticus faktorok működészavarát több szerző is erősen valószínűsíti [12,[23][24][25]. Míg állatkísérletekben első-sorban a VEGF-A csökkent működése eredményezte IUGR kialakulását, addig a humán mintán végzett vizsgálatok elsősorban a PlGF érintettségére utaló eredmé-nyeket mutattak [26][27][28][29][30].…”
Section: Vascular Endothelial Growth Factor a (Vegf-a)unclassified
“…Antiangiogenic compounds have been associated with defective luteogenesis, reproductive dysfunction, pregnancy loss, and teratogenesis (41)(42)(43). Previous studies have reported TEM1 expression in several tissues of the mouse embryo (22,44).…”
Section: Tem1-tt Vaccination Induces T Cell Responses Against Tumor-amentioning
confidence: 99%